A preliminary study on the Mesozoic massive gold metallogenic mechanism of the deep-large fault coupling with critical water in the Jiaodong area, China - HU Baoqun; GAO Haidong; WANG Yun; ZHANG Baolin; LYU Guxian (Dizhi lixue xuebao, 2021)
This study aims to study the reason why a huge accumulation of gold deposits occurred in the Jiaodong area. We summarized and analyzed the geological background and metallogenic characteristics of the Jiaodong gold deposits. In parallel, we highlighted the importance of depressurization-driven movement of ore-forming materials at two stages and the special properties of critical water (water at the critical value of both temperature and pressure, the same below) based on the theory of water phase change controlling metallogenesis in hydrothermal deposits. The above analysis results allow us to propose the Mesozoic massive gold metallogenic mechanism of deep-large fault coupling with critical water in the Jiaodong area, that is, the metallogenic mechanism of "one cake plus one knife". The old metamorphic rocks provide abundant ore-forming materials. In the early stage, a large-scale point-like depressurization results in acid intrusive complexes and various dykes, which were accompanied by a large amount of critical water over a long time to promote the activation and migration of ore-forming materials; In the late stage, the depressurization of the large linear fault caused the precipitation of ore-forming materials in a short time. The faults with open discontinuous space are dominated by ore-filling structures, while the fracture zones with continuous space are dominated by mineralized alteration with metasomatic structures. Abundant gold in metamorphic rocks, two stages of depressurization with different properties and unique properties of critical water are the main factors for the accumulation of massive gold deposits in the Jiaodong area.